Effects of root zone temperature and light intensity on plant growth, flowering and fruit quality of plant factory ‘festival’ strawberry (Fragaria × ananassa Duch.) - M., Munirah; Abdullah, S.A.; Kassim, R.; Masnira, M.Y.; Sakinah, I.; Ahmad, M.A.; Tajidin, N.E. (Rynnye Lyan Resources, 2024)
The growth and production of strawberries in a plant factory are highly affected by environmental factors such as light and temperature. Recent interest in plant factory production of strawberries in soilless substrates has raised concerns about the potential effects of root zone temperature (RZT) and light intensity on plant growth and fruit yields. The hypothesis suggests that RZT and light intensity can improve plant growth and affect flower production. This study aimed to investigate the effects of RZT and light intensity on the growth and reproductive performance of strawberries. The root zone of the 'Festival' strawberry plants was subjected to a temperature of 15°C during the night for root zone cooling (RZC) treatment meanwhile without RZT as the control, under two different light intensities: 200 mmolm-2s-1 and 300 mmolm-2s-1. From the result, the root and crown temperatures in the RZC treatment were maintained at 15-21°C. The number of leaves was significantly affected by the interaction between RZT and light intensity. The crown diameter in the RZC treatment group (13.27 cm) was higher than in the control group (12.06 cm). Higher light intensity (356.9 mmolm-2s-1) significantly increased the chlorophyll content. Flower production in the RZC treatment was 52% higher than in the control group. The enumeration of growth organs and flowers increased in the RZC treatment, suggesting the induction of reproductive growth by the low root zone temperature. However, the light intensity received by the plants and the interaction between RZC and light intensity did not have any effect on flower production. Fruit size, fruit pH, fruit firmness and total soluble solids: titratable acidity were not affected by RZT, light intensity, or the interaction between RZT and light intensity. The increase in flower production can be attributed to the lower plant temperature, specifically at the crown, which was at 10-12°C. In conclusion, RZC can induce growth and reproductive performance, ultimately increasing the fruit yield of hydroponically cultivated strawberries in a plant factory.